Sistemas baseados em amido termoplástico: pectina contendo hidroxiapatita nanoestruturada visando liberação de fósforo em meio aquoso - Santos, Maria Fernanda dos (Universidade Federal de São Carlos, 2013)
The use of fertilizers to increase agricultural production, combined to the high import rate of this resource by Brazil, has motivated scientific and technological development of high performance fertilizers. In this context, here we aimed at the synthesize hydroxyapatite nanoparticles (HAP) by coprecipitation method followed by hydrothermal treatment. HAP solubility obtained at different hydrothermal aging was evaluated to monitor the dependence of solubility in aqueous solution with particle size and crystallization condition. In order to control the release of phosphate ions from HAP, aiming at application in soil as a fertilizing resource, the methodology used was based on placing the nanoparticles inside sachets-like compartments. Such sachets are composed by polymeric films containing different percentages of thermoplastic starch (TPS) and pectin (PEC). The best composition of the blends was determined by investigating the degradation of sachets in aqueous solution. The solubility of the HAP nanoparticles was evaluated by measuring the concentration of phosphate ions in aqueous solution, using the molybdenum blue colorimetric method. The results showed that the nanoparticles without hydrothermal treatment presented high solubility, lower particle size and crystallinity. After storage inside the polymeric sachet, it was observed that both the nanoparticles with and without hydrothermal treatment have high solubility, which may be due to a decrease in the pH caused by polymer degradation. From these results it was concluded that the incorporation of HAP inside the polymeric sachets could be an alternative to minimize the effects of leaching and provide controlled release of phosphorus, since the polymers employed (starch and pectin) show high biodegradability.
Keywords: Biotecnologia; Amido termoplástico; Blendas poliméricas; Hidroxiapatita; Pectina; Solubilidade; OUTROS